Unification and Finite Model Property for Linear Step-Like Temporal Multi-Agent Logic with the Universal Modality - Bashmakov, Stepan I.; Zvereva, Tatyana Yu. (Bulletin of the Section of Logic, 2022)
This paper proposes a semantic description of the linear step-like temporal multi-agent logic with the universal modality \(\mathcal{LTK}.sl_U\) based on the idea of non-reflexive non-transitive nature of time. We proved a finite model property and projective unification for this logic.